Tanda-án forgetting stigma, remembering home in a dementia village designed for Filipino communities - Olap, Kayla Gabrielle Navarez (College of Architecture, University of the Philippines Diliman, 2025)
This research explores the adaptation of the dementia village model in the Philippine context, aiming to address the challenges faced by existing care models and reduce the societal stigma associated with utang na loob regarding placing elderly family members in care facilities. Moreover, the study aims to incorporate Filipino cultures and to optimize the architectural design of the village for the tropical climate. Using a mixed-methods approach, the study combines quantitative and qualitative data from semi-structured interviews with high-risked individuals and consultations with local experts in architecture and neurology. The findings highlight the importance of integrating traditional architectural design and Filipino cultural elements, such as spaces for religious activities and family visits, into the dementia village design. Furthermore, the research underscores the need for biophilic and sustainable design strategies to address the environmental challenges of the tropical climate. Ultimately, this research provides a framework for a culturally-sensitive, climate-responsive dementia village that not only enhances the quality of care of elderly residents but also helps alleviate the emotional, physical, and financial burden of Filipino families. The study contributes to the growing body of knowledge on dementia care in developing countries, offering design solutions that are both practical and deeply rooted in local cultural values.